HYPOFRACTIONATED RADIOTHERAPY FOR MACROSCOPIC CANINE SOFT TISSUE SARCOMA: A RETROSPECTIVE STUDY OF 50 CASES TREATED WITH A 5 × 6 GY PROTOCOL WITH OR WITHOUT METRONOMIC CHEMOTHERAPY. Issue 1 (9th November 2015) - Cancedda, Simona; Marconato, Laura; Meier, Valeria; Laganga, Paola; Roos, Malgorzata; Leone, Vito F.; Rossi, Federica; Bley, Carla Rohrer
Abstract : Wide surgical resection or a marginal/incomplete resection followed by full‐course radiation therapy is the current standard of care for canine soft tissue sarcoma. The purpose of this retrospective, descriptive, bi‐institutional study was to determine the effectiveness and toxicity of a hypofractionated 5 × 6 Gy protocol on macroscopic canine soft tissue sarcoma in terms of progression‐free interval (PFI) and overall survival (OS), and to identify prognostic factors for patient outcome. Dogs with macroscopic soft tissue sarcoma irradiated with 5 × 6 Gy were eligible for the study. Progression‐free interval and OS were compared with respect to different tumor and patient characteristics by the Kaplan–Meier method and multivariable Cox regression analysis. Fifty dogs with macroscopic disease were included. All dogs received the same radiation therapy protocol; part of the group ( n = 20) received postradiation metronomic chemotherapy. Median PFI for all cases was 419 days (95% confidence interval (CI): 287–551) and median OS was 513 days (95% CI: 368–658). Dogs with tumors on the limbs had significantly longer PFI and OS, compared with head or trunk. Increasing tumor burden decreased OS. The addition of metronomic chemotherapy yielded a significantly longer OS (757 days (95% CI: 570–944) compared with dogs that did not receive systemic treatment (286 days (95% CI: 0–518), ( P = 0.023)), but did not influence progression‐free interval. Toxicity was low throughout all treatments. The 5 × 6 Gy radiation therapy protocol was well tolerated and provided long PFI and OS in dogs with macroscopic soft tissue sarcoma.